Institutional transfer: industrial relations in Eastern Germany - Richard Hyman (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
Can industrial relations be successfully transferred between countries. Thispaper reviews experience in eastern Germany since unification in 1990. Theevidence is that the close integration in western Germany between the twoelements of the 'dual system' of interest representation - trade unions andworks councils - has not been replicated in the east. Hence the formalidentity of institutions does not prevent substantial differences in theirfunctioning. This may be explained both in terms of the adverse economiccircumstances in the east since unification, and of the distinctive socio-cultural inheritance of the former system. – – Kann ein System industrieller Beziehungen erfolgreich von einem Land in einanderes übertragen werden. In dem Papier wird der entsprechende Prozeß in Ostdeutschland seit der Vereinigung untersucht. Dabei wird offenkundig,daß der enge Zusammenhang des Doppel-Systems der Arbeitnehmervertretung im Westen Deutschlands - Gewerkschaften und Betriebsräte - sich im Osten nicht wiederholt hat. Ganz im Gegenteil: Dieformale Gleichheit dieser institutionellen Regelungen steht substantiellen Unterschieden in der Umsetzung nicht entgegen. Dies kann sowohl durch diekritischen wirtschaftlichen Rahmenbedingungen als auch durch die starke soziokulturelle Prägung aus DDR-Zeiten erklärt werden.
Keywords: 330; Arbeitsbeziehungen; Institutioneller Wandel; Neue Bundesländer